Cell Network-Based Formulas for Fast Determination of Flexural Stiffness Reduction of U-Shaped Core Shear Walls. Issue 2 (May 2018) - Yang, Yicheng; Yemmaleni, Sai; Song, Ikkyun; Cho, In Ho
Reinforced concrete (RC) core shear wall is one of the most widely used earthquake-resisting systems. Degradation of a core wall's flexural stiffness is vital for understanding the natural frequency shift of the damaged building. But it is hard to capture, often necessitating complex finite element analyses (FEAs). This study seeks to provide an efficient tool to quickly determine the remaining flexural stiffness of U-shaped core walls. Importantly, the tool is designed to require only the easy-to-collect observational damage information. Of primary novelty is a network of microscopic unit cells, each consisting of nonlinear concrete and steel springs along with a compression-only gap. Validations with three U-shaped walls tested under complex and multidirectional loading paths show that the proposed formulas appear promising in quickly determining the trend of degrading flexural stiffness compared with a high-precision multiscale FEA program. All the formulas written in Matlab codes are made publicly available. Using the portable formulas running on a laptop, practicing engineers and researchers will be able to swiftly diagnose core U-shaped walls after quick on-site or laboratory observations.